2016
DOI: 10.1007/s11581-016-1748-4
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of N-doped carbon nanosheet-encased cobalt nanoparticles as efficient oxygen reduction catalysts in alkaline and acidic media

Abstract: In this work, a low-cost, high-performance, and environmentally friendly non-precious-metal catalyst was fabricated via a simple pyrolysis of the corn starch, dicyandiamide, and cobalt acetate for the oxygen reduction reaction (ORR). Scanning electron microscope (SEM) and transmission electron microscopy (TEM) images show that the catalyst has porous and graphene-like carbon nanosheetencased metal nanoparticles structure. Electrochemical measurements show that, compared to the commercial Pt/C catalysts, the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 56 publications
1
2
0
Order By: Relevance
“…It was found that the commercial Pt/C catalyst gave the highest onset potential in alkaline medium, which is 0.95 V. e onset potential reduced to 0.87 V for both Fe-NCNT and Co-NCNT catalyst. e small di erence (80 mV) between of the onset potential between the commercial Pt/C catalyst and the NPM catalysts synthesized in this study was also shown in previous studies reported on the non-precious metal N-doped carbon based catalyst for which the ORR activity was comparable with the commercial Pt/C catalyst in alkaline medium (Yao et al, 2015;Zhao et al, 2016;Ratso et al, 2016b). In addition, the onset potential di erence between these NPM catalysts with the Pt/C catalyst is less under the alkaline condition as compared with the acidic condition reported in a previous work (Abd Lah Halim et al, 2019).…”
Section: Electrochemical Characterizationsupporting
confidence: 85%
“…It was found that the commercial Pt/C catalyst gave the highest onset potential in alkaline medium, which is 0.95 V. e onset potential reduced to 0.87 V for both Fe-NCNT and Co-NCNT catalyst. e small di erence (80 mV) between of the onset potential between the commercial Pt/C catalyst and the NPM catalysts synthesized in this study was also shown in previous studies reported on the non-precious metal N-doped carbon based catalyst for which the ORR activity was comparable with the commercial Pt/C catalyst in alkaline medium (Yao et al, 2015;Zhao et al, 2016;Ratso et al, 2016b). In addition, the onset potential di erence between these NPM catalysts with the Pt/C catalyst is less under the alkaline condition as compared with the acidic condition reported in a previous work (Abd Lah Halim et al, 2019).…”
Section: Electrochemical Characterizationsupporting
confidence: 85%
“…Metal–air batteries with promising sustainable energy conversion are highly dependent on the activity and stability of the cathodic oxygen reduction reaction (ORR) and anodic oxygen evolution reaction (OER). Platinum (Pt)-based materials have been identified as the best performing ORR catalysts, whereas Ru- and Ir-based catalysts are effective in the OER process. However, these noble-metal-containing catalysts are plagued by scarcity, high price, and limited stability, which inspire researchers to seek effective, highly active, and durable bifunctional electrocatalysts for ORR and OER. …”
mentioning
confidence: 99%
“…33,50 Co 2+ with a binding energy of 780.8 eV was reported to be due to Co–N bonds, corresponding to the appearance of Co–N in the N 1s energy level. 30,51,52 Thereafter, the relative percentage of Co 2+ and metallic Co in Co@NC and Co@NC-CNT calculated according to their area is 26.7%, 2.2 at% and 42.7%, 2.8 at%, respectively, indicating that most cobalt atoms on the surface of the catalysts exist in the oxidized state. Besides, the percentage of Co 2+ in Co@NC-CNT is higher than that of Co@NC, indicating that the electron interaction of Co with N in Co@NC-CNT is much stronger than that in Co@NC.…”
Section: Resultsmentioning
confidence: 98%